Variations of Growing Media and Light Emitting Diode (LED) Colors in Red Spinach Microgreens - Kartika Sari, Vega; Kristiyanti Putri, Widya; Hidayatullah, Raihan; Basuki (Journal of Soilscape and Agriculture, 2024)
Microgreens have higher nutrition than mature plants. Microgreens are popular for garnishing dishes and are a choice for those living a healthy life. Red spinach microgreens are preferred and contain many vitamins. The type of the growing media used will influence the growth of microgreens. Growing media can vary in texture, nutrient, and mineral content. Lighting also required by microgreens may require choosing the right type of LED light color because generally microgreen cultivation is indoor. The aims of this research is to determine the growth of red spinach microgreens on various types of growing media and on several types of LED colors. The result showed that, the best results for germination, plant height, and number of leaves are red and blue LEDs on all media, while for the best fresh weight using red LEDs on sand-compost media.